Does Entrepreneurship Education Determine Entrepreneurial Motivation among University Graduates: An Empirical Investigation - Mathew Ekundayo Rotimi; Joseph Ojo Ise Olorunkanmi; Grace Gift Rotimi; Mishelle Doorasamy (Jurnal Ekonomi, Bisnis & Entrepreneurship, 2022)
The study seeks to know if the acquired knowledge from entrepreneurship education offered in the university enhances and moderates entrepreneurship competencies on entrepreneurial motivation. The study employs both qualitative interviews and a cross-sectional survey of a sample of 300 graduates cutting across different faculties. The study finds that entrepreneurship education is a requisite to entrepreneurship motivation. It also reveals that entrepreneurship motivation could be predicted through entrepreneurship competencies. Contrary to the common belief that entrepreneurship education is a requisite to entrepreneurship motivation and competencies, this study reveals otherwise. It shows that entrepreneurship education does not account for graduate’s motivation to becoming entrepreneurs.The study recommends that the entrepreneurship education should be directed towards developing the psychology of graduates along the path of entrepreneurship to boost entrepreneurial motivation, skills, and critical thought. The study contributes to research on entrepreneurship. Specifically, it seeks to find out if the acquired knowledge from entrepreneurship education influences entrepreneurship competencies on entrepreneurial motivation.